INOVASI PEMBELAJARAN TERINTEGRASI KEARIFAN LOKAL JAMBI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF MAHASISWA - Iriani, Dewi; Susanti, Nova; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2022)
This study aims to improve physics education students' ability to think creatively and critically. The Project Based Learning model was chosen as a solution found by researchers in the field regarding the low ability of students to think creatively and critically, seen from making their paper assignments and displaying their PowerPoint presentations, how to ask and answer questions in Micro-Learning courses. This Classroom Action Research (CAR) is carried out in 3 cycles. Each cycle consists of planning, Action Implementation, Observation, Analysis, and Reflection. The data collection techniques were observation, interviews, documentary, and literature studies. The results showed that using the Jambi local wisdom-based Project Based Learning Model in Micro-Learning Courses can Improve Students' Creative and Critical Thinking Abilities. The percentage of students with the ability to think creatively in cycle I was 37.5. In cycle II the percentage increased to 56.8, and in cycle III, the percentage increased to 91.1. Meanwhile, the ability to think critically experienced an increase in cycle I, the percentage obtained was 36.0. In cycle II the percentage was 59.8, and in cycle three, it increased to 80.4.